Analisis Disiplin Kerja Pada Peningkatan Kinerja Guru Di SDN Sukasari: (Studi Di Desa Sukasari, Kecamatan Gunung Halu) - Rustandi, Tendi; Jaelani, Dede (Politeknik Negeri Ambon, 2024)
This study aims to determine the implementation of work discipline among SDN Sukasari teachers. This includes how work discipline has been well implemented at SDN Sukasari School, which aims to find out how the role of work discipline can improve teacher performance. This research uses a qualitative approach with a descriptive method. Researchers use their main tools to study the state of natural objects, use triangulation (observation, interviews, and documentation), obtain qualitative data, analyze data inductively or qualitatively, and produce findings. The results of this study show the role of work discipline in improving teacher performance at SDN Sukasari. This is shown by the results of interviews and observations of work-discipline roles that have been carried out well. This research provides an in-depth picture of how work discipline can improve teacher performance in these institutions. The work discipline of teachers also has a positive impact on the relationship between teachers and their students. They can also manage time better, which helps them complete tasks better. To maintain work discipline at SDN Sukasari School, regulations regarding working hours, lateness, and absenteeism have been made. The purpose of these regulations is to ensure that teachers have the expected behavior and performance.